Mechanika : creating the art of space, aliens, robots and sci-fi - Chiang, Doug (Cincinnati, Ohio : Impact, 2015)
"In a post-apocalyptic alien landscape, starfighters crash land in desert terrain, dino riders rear up, rusted crab walkers litter the horizon and men work with--or fight against--giant iron robots. You control it all and Academy Award-winning sci-fi film production designer Doug Chiang tells you how. In this revised and updated version of his best-selling book, Mechanika, Chiang uses his 25 years in the film industry working on such films as the Star Wars franchise, Terminator 2: Judgment Day and War of the Worlds to teach you the techniques, tools and tips to draw and think like a master sci-fi artist." --
Includes index.
Keywords: Fantasy in art; Science fiction in art; Drawing -- Technique; Painting -- Technique; Computer art -- Technique